2019
DOI: 10.1111/anae.14636
|View full text |Cite
|
Sign up to set email alerts
|

Associations of nadir haemoglobin level and red blood cell transfusion with mortality and length of stay in surgical specialties: a retrospective cohort study

Abstract: Few studies have investigated if, and how, red cell transfusion and anaemia interact. We analysed 60,955 admissions to three metropolitan hospitals in Western Australia between 2008 and 2017 to determine whether the relationship between red cell transfusion and outcomes in surgical patients differed by lowest (nadir) level of haemoglobin. At levels above 100 g.l À1 , in-hospital, 30-day and 1-year mortality were higher with transfusion, the adjusted odds ratios (ORs) (95%CI) being 8.80 (4.43-17.45) p < 0.001 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Furthermore, several literatures reported that blood transfusion is associated with adverse outcomes perioperatively [8][9][10]. Furthermore, data obtained from two large multicenter databases of 23,348 patients [11], and 227,425 patients [12] demonstrated that not only severe but also moderate/mild preoperative anemia is an independent risk factor for postoperative morbidity and 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several literatures reported that blood transfusion is associated with adverse outcomes perioperatively [8][9][10]. Furthermore, data obtained from two large multicenter databases of 23,348 patients [11], and 227,425 patients [12] demonstrated that not only severe but also moderate/mild preoperative anemia is an independent risk factor for postoperative morbidity and 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The trigger threshold for blood transfusion varies across different institutions and remains a matter of debate 10 . Moreover, it was recently reported that nadir haemoglobin affected the relationship between red blood cell transfusion and outcomes, 21 which indicates that the optimal haemoglobin level may vary between patients. Thus, merely relying on a patient's haemoglobin level to trigger blood transfusion is imprecise and incomprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…The trigger threshold for blood transfusion varies in different institutions and remains a matter of debate [10]. Moreover, it was recently reported that nadir hemoglobin affected the relationship between red cell transfusion and outcomes [20], which indicated that the optimal hemoglobin level might vary in different patients. Thus, merely using hemoglobin level to direct blood transfusion is imprecise and incomprehensive.…”
Section: Discussionmentioning
confidence: 99%